Pengembangan Ensiklopedia Keanekaragaman Hayati Di Kabupaten Jepara Sebagai Suplemen Bahan Ajar Untuk Meningkatkan Hasil Belajar Dan Sikap Konservasi Lingkungan - Rifana Habiba; Sri Ngabekti; Dyah Rini Indriyanti (Departement of Mathematics Education, 2023)
This research analyzed the characteristics, reliability validity, practicability, and effectiveness of an encyclopedia. This Research & Development applied a 4-D model, starting from defining, designing, developing, and disseminating. This research applied a one-group pretest-posttest design. The subjects were 70 learners from the tenth grade of the Mathematics and Science Program in Jepara Regency. The researchers collected with an expert validation questionnaire, readability questionnaire, and encyclopedia practicability questionnaire. The researchers also used twenty multiple-choice items. The developed product contained living creature diversity in the Jepara regency, such as plants and animals from the genus level, type, and ecosystem. The product also consisted of the steps to take the benefits of biodiversity for the surrounding people. The efforts of taking benefits included land management for agriculture, rice field, gum field, corn field, and cassava fields. The development in Jepara seemed to be contextual and factual with the learner necessity orientation. The encyclopedia design was attractive for the learners to understand biodiversity. The product also had a systematic arrangement based on the learning indicators. The data of the experts' validations were: 82.4% by the material expert and 84% by the media expert. Thus, the product was valid and reliable to use in learning. The readability results by the teachers obtained a percentage of 94.35% while the learners obtained a percentage of 86.22% with the excellent category. Thus, the encyclopedia was understandable and readable excellently by the teachers and the learners. The practicability data of the encyclopedia, by the teachers, obtained a mean percentage of 91.67%, categorized as practical. The result indicated the developed encyclopedia was easy to use and could facilitate the learners in learning biodiversity. The effectiveness of the teaching material was based on the classical accomplishment, N-gain, and the questionnaire on conservation attitude. The classical accomplishment of the learners' learning outcomes after learning with the media was 91%. The percentage indicates classical accomplishment. The N-gain score was 0.30, categorized as moderate. The value indicated the teaching material was effective to improve the learners' learning outcomes. The assessment on conservation attitude obtained a category of very excellent with a mean percentage of 3.56%. Thus, the researcher concluded the developed encyclopedia about biodiversity as a teaching material supplement was valid and reliable to apply in learning. The product was also effective to improve the learning result and the learners' conservation attitudes.